2012
DOI: 10.1371/journal.pone.0043894
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Landscape Variables on the Species-Area Relationship during Late-Stage Habitat Fragmentation

Abstract: Few studies have focused explicitly on the later stages of the fragmentation process, or “late-stage fragmentation”, during which habitat area and patch number decrease simultaneously. This lack of attention is despite the fact that many of the anthropogenically fragmented habitats around the world are, or soon will be, in late-stage fragmentation. Understanding the ecological processes and patterns that occur in late-stage fragmentation is critical to protect the species richness in these fragments. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 73 publications
(81 reference statements)
1
28
1
Order By: Relevance
“…The lack of support for the predicted dominance of SL > SS based on minimum patch size requirements also suggests that Tjørve's (2010) prediction of higher species density on large patches than small patches is likely not supported. This is at least qualitatively consistent with the fact that, among the papers in my SLOSS empirical review that included estimates of species density (in addition to species number per patch), Acosta and Robertson (2002) found higher fish species density on small than large reef patches, Arroyo-Rodríguez, Pidena, Escobar, and Benítez-Malvido (2009) found higher plant species density in small than large forest patches, and Leavesley and Cary (2013) and Hernandez-Ruedas et al (2014) found no difference in species density between small and large patches for birds and trees in forest patches, respectively.…”
Section: Minimum Patch Size Selective Extinction and Nestednesssupporting
confidence: 71%
See 2 more Smart Citations
“…The lack of support for the predicted dominance of SL > SS based on minimum patch size requirements also suggests that Tjørve's (2010) prediction of higher species density on large patches than small patches is likely not supported. This is at least qualitatively consistent with the fact that, among the papers in my SLOSS empirical review that included estimates of species density (in addition to species number per patch), Acosta and Robertson (2002) found higher fish species density on small than large reef patches, Arroyo-Rodríguez, Pidena, Escobar, and Benítez-Malvido (2009) found higher plant species density in small than large forest patches, and Leavesley and Cary (2013) and Hernandez-Ruedas et al (2014) found no difference in species density between small and large patches for birds and trees in forest patches, respectively.…”
Section: Minimum Patch Size Selective Extinction and Nestednesssupporting
confidence: 71%
“…Given the predominance of SS > SL, May et al’s species‐clumping argument predicts that in most SLOSS comparisons to date, most species distributions are clumped at a spatial scale that is relevant to the scale of patchiness following habitat removal . Note that species clumping independent of habitat heterogeneity might explain why some studies in my empirical review found SS > SL even in a homogeneous environment or where SL were more heterogeneous than SS (Abele & Patton, ; Báldi & Kisbenedek, ; Gavish et al, ; Hu et al, ; O'Connell & Bolger, ; Robinson & Quinn, ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…small isolated patches constrain species to survive within small local populations (McGarigal and Marks, 1995;Fahrig, 2003;Fischer and Lindenmayer, 2007). However, at the landscape level, changes in species richness may be predicted along environmental gradients (McGarigal et al, 2005;Schindler et al, 2008) and habitat fragmentation and loss are considered as major determinants of biodiversity decline worldwide (Schindler et al, 2008;Hu et al, 2012). Intensive land uses for agricultural purposes lead to fragmented natural habitats resulting in smaller and more isolated patches (Hoffmann and Greef, 2003;Morelli, 2013;Ramesh et al, 2015), which in turn reduce habitat connectivity, inhibit animal movements and ecological processes (Kozakiewicz, 1993;Crooks et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Landscapes with more forest cover support a larger species pool (Hu et al 2012, Taylor et al 2012) through both sampling effects (Wiens 1992, Whittaker andFernández-Palacios 2007) and because a greater forest extent offers habitat diversity (Radford et al 2005, Maron et al 2012. Several empirical studies have shown that sites in landscapes with more forest support higher densities of reptiles (McAlpine et al 2015), greater species richness and abundance of birds (Villard et al 1999, Mortelliti et al 2010, Martensen et al 2012, Taylor et al 2012, and greater richness of small mammals (McAlpine et al 2006, Estavillo et al 2013).…”
Section: Extent Of Forest and Species Richnessmentioning
confidence: 99%